Características de qualidade da carne de ovinos de diferentes genótipos e idades ao abate - Silva Sobrinho, Américo Garcia da [UNESP]; Purchas, Roger Walter; Kadim, Isam Tawfik; Yamamoto, Sandra Mari [UNESP] (Sociedade Brasileira de Zootecnia, 2005)
Cordeiros criados em regime de pasto, provenientes de ovelhas Romney acasaladas com três raças paternas (Romney, East Friesian x (Finn x Texel) e Finn x Poll Dorset), foram avaliados quanto às características de qualidade da carne. Os cordeiros foram abatidos aos 150 e 300 dias de idade, cada lote com 15 animais de cada raça paterna, totalizando 90 animais. A carne dos cordeiros Romney foi mais macia que a dos demais genótipos. O pH final do músculo Semimembranosus dos cordeiros abatidos mais precocemente foi superior (5,61) ao dos abatidos mais tardiamente (5,58), entretanto estes últimos apresentaram carne com menor maciez (11,16 kg) que os abatidos aos 150 dias de idade (7,45 kg). Com relação à cor, a luminosidade da carne de cordeiros abatidos aos 150 dias foi maior (38,20) que a dos abatidos mais tardiamente (36,80), mas não foi afetada pelo genótipo. Concluiu-se que o genótipo e a idade de abate influíram na produção e qualidade da carne ovina.

Lambs born from Romney ewes and sired by Romney, East Friesian x (Finn x Texel), and Finn x Poll Dorset, under pasture grazing system, were evaluated for meat quality. Animals were slaughtered at two age groups (150 and 300 days), each group with 15 animals of each sire breed, in a total of 90 animals. The meat from Romney lambs was more tenderness than those from the other genotypes. The final pH in semimembranosus muscle of younger lambs was higher (5.61) than those in muscle from older lambs (5.58). But, these last showed meat less tenderness (11.16 kg) than that from lambs slaughtered at 150 days of age (7.45 kg). In relation to meat color, the luminosity of meat from lambs slaughtered at 150 days was higher (38.20) than that from lambs slaughtered later (36.80), but this trait was not affected by genotype. In conclusion, both genotype and slaughter age influenced quantitative aspects of lamb carcass and lamb meat quality characteristics.
Meat quality in lambs of different genotypes and ages at slaughter
Keywords: meat; qualitative aspects; Lamb; carne; qualidade; Ovinos